TOURIST PERCEPTIONS BASED ON PUSH FACTOR AND HEALTH PROTOCOL IN TAMAN SATWA LEMBAH HIJAU LAMPUNG - Santa Togi Maritona; Sugeng P Harianto; Bainah Sari Dewi; Gunardi Djoko Winarno (Journal of People, Forest and Environment, 2022)
Visitors' perceptions of tourism objects are very valuable because they can be used by managers as a source of tourism development planning. This study aims to determine visitor perceptions based on push factors and the application of health protocols by visitors. This research was conducted from October-November 2021 with the research location in the Lembah Hijau Wildlife Park, Lampung. The research method is interviews with 100 respondents based on the Slovin formula (1960). Descriptive data analysis and Likert scale analysis. The results of the study of visitor perceptions based on the push factor got a fairly attractive category with a Likert scale of 3.86 because the ticket prices were still considered not cheap by visitors. Factors that encourage visitors to visit are animal shows, free flight bird shows, taking photos with birds, and visitors being able to ride elephants and feed elephants. Visitors' perceptions based on the application of health protocols get a good category with a Likert scale of 4.07. During their visit, visitors always wear masks, wash their hands in the places provided, keep their distance, and reduce interactions with other visitors as part of implementing health protocols.